Influx of illegal immigrant: issues and challenges in Malaysia / Ahmad Adha Amir Yassser Amri and Muhammad Aidil Azeman. - Amri, Ahmad Adha Amir Yassser; Azeman, Muhammad Aidil (2005)
For the past few years, the issue of influx of illegal immigrants has been a milestone matter in our country. This never-ending problem has caused a lot of burden to our government as it is hard to handle due to high number of illegal immigrants. Billions of Malaysian Ringgit has been spent and the problem keep continue to arise. This had affected our relationship with our neighbour especially Indonesia as they hold the largest group of illegal immigrants in Malaysia. Measures are taken from the early 1990s however it has become more difficult because the Malaysian coastline and border is far too long to be patrolled effectively by the marine police and immigration personnel who are limited in number. The difficulty is further compounded by public apathy and abetment induced by socio-cultural or economic reasons. Therefore it has come to Malaysian Government concern that an even higher degree of measures and improvement to our legal sanction need to be taken immediately.